Polylactide-co-glycolide nanoparticles of antitubercular drugs: formulation, characterization and biodistribution studies. (December 2014) - Chawla, Ruchi; Solanki, Harshendra S; Kheruka, Subhash Chand; Gambhir, Sanjay; Dube, Veeresh; Aggarwal, Lalit M; Mishra, Brahmeshwar
Background: The present study was designed to prepare and characterize poly lactide-co-glycolide nanoparticles of antitubercular drugs (ATDs) for delivery through oral route to alveolar macrophages.Methods: Nanoparticles were prepared by double emulsification solvent evaporation method. Ex vivo and in vivo drug accumulation studies were performed in alveolar macrophages, harvested by broncheoalveolar lavaging. Internalization of nanoparticles was studied by confocal laser scanning microscopy. γ-scintigraphy imaging using technetium-99m was done to study the biodistribution pattern of nanoparticles.Results: High intracellular concentrations of ATDs were observed in macrophages within 30 min of administration of nanoparticles. Intense radioactivity recorded in liver, spleen and lungs revealed uptake of nanoparticles in macrophages, abundantly present in mononuclear phagocyte system present in these organs.Conclusion: Targeted delivery of ATDs will help reduce dose and associated side effects including hepatotoxicity of ATDs. Further studies are required to assess the potential therapeutic advantages for treatment of TB.